2022
DOI: 10.1155/2022/6022380
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Opioid Consumption with Pericapsular Nerve Group Block for Hip Surgery: A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: The pericapsular nerve group (PENG) block targets the nerves innervating the anterior hip surface; however, few studies on this technique are currently available. We investigated the effects of the PENG block on postoperative opioid consumption after a hip surgery. This was a randomized, double-blind, placebo-controlled study conducted at a single institution. Fifty patients undergoing hip surgery were randomly allocated, 25 in each group, to receive a PENG block either using 25 mL of 0.5% ropivacaine (PENG gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Patient satisfaction was observed by their willingness to accept the block in the future, which was better in the PENG group (94%) than in the FNB group (77%). This was similar to other studies that have observed good patient satisfaction scores [ 20 , 25 , 26 ]. There were no significant hemodynamic changes or block-related adverse effects in both groups.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Patient satisfaction was observed by their willingness to accept the block in the future, which was better in the PENG group (94%) than in the FNB group (77%). This was similar to other studies that have observed good patient satisfaction scores [ 20 , 25 , 26 ]. There were no significant hemodynamic changes or block-related adverse effects in both groups.…”
Section: Discussionsupporting
confidence: 92%
“…In yet another cohort study performed by Sahoo et al, USG-guided PENG block was administered to 20 consecutive patients posted for hip fracture surgeries and inferred significant drop of six to seven points in VAS scores at rest (baseline: 7.45 ± 1.53; 30 minutes after block: 1.1 ± 1.07) and with movement (baseline: 9.45 ± 0.75; 30 minutes after block: 2.35 ± 1.34) during positioning the patients for SA [ 25 ]. There are many other case series, placebo-controlled trials with PENG block, and trials comparing PENG with other established blocks like fascia iliaca block demonstrating similar results [ 14 , 18 , 26 - 30 ].…”
Section: Discussionmentioning
confidence: 92%
“…It has shown decreased opioid consumption in the first 24 h postoperatively and decreased pain scores in the short-term postoperative period and post-anesthesia care unit after open hip surgeries compared to sham block and compared to conventional postoperative analgesia. 21 , 25 , 26 …”
Section: Discussionmentioning
confidence: 99%
“…More importantly, the PENG block blocks only the joint branches of the nerves, causing no motor impairment, and promotes early postoperative ambulation, lowering the likelihood of serious problems such as thrombosis of the deep veins and enhancing postoperative recovery quality. 11 Incisional pain is also a significant source of postoperative pain in patients with AHS. The lateral femoral cutaneous nerve block (LFCN) provides most of the cutaneous innervation to the surgical site.…”
Section: Introductionmentioning
confidence: 99%